1993
DOI: 10.1159/000217834
|View full text |Cite
|
Sign up to set email alerts
|

Factors Controlling Pancreatic Islet Neogenesis

Abstract: We have established a model in which cellophane wrapping induces reiteration of the normal ontogeny of β-cell differentiation from ductal tissue. The secretion of insulin is physiologic and coordinated to the needs of the animal. Streptozotocin-induced diabetes in hamsters can be ‘cured’ at least half the time. There appears to be activation of growth factor(s) within the pancreas acting in an autocrine, paracrine or juxtacrine manner to induce ductal cell proliferation and differentiation into functioning β-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…The role played by the DEC in our study is akin to the regulatory one it performs in the normal pancreas, where the relationship between the ductal and endocrine pancreatic components begins in embryonic development with the budding of the primordial ductal epithelium and the emergence of primitive islets [31,32]. The phenotypic maturation and differentiation of these cellular aggregates requires signals supplied by adjacent cells, which take the form of soluble, trophic factors released in a paracrine fashion [33,34]. This cellular inter-relationship is conserved in adulthood; maintenance of beta cell mass and remodelling occurs due to constant, yet limited, islet neogenesis [35], again under the influence of soluble factors derived from the ductal epithelium [34,36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role played by the DEC in our study is akin to the regulatory one it performs in the normal pancreas, where the relationship between the ductal and endocrine pancreatic components begins in embryonic development with the budding of the primordial ductal epithelium and the emergence of primitive islets [31,32]. The phenotypic maturation and differentiation of these cellular aggregates requires signals supplied by adjacent cells, which take the form of soluble, trophic factors released in a paracrine fashion [33,34]. This cellular inter-relationship is conserved in adulthood; maintenance of beta cell mass and remodelling occurs due to constant, yet limited, islet neogenesis [35], again under the influence of soluble factors derived from the ductal epithelium [34,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic maturation and differentiation of these cellular aggregates requires signals supplied by adjacent cells, which take the form of soluble, trophic factors released in a paracrine fashion [33,34]. This cellular inter-relationship is conserved in adulthood; maintenance of beta cell mass and remodelling occurs due to constant, yet limited, islet neogenesis [35], again under the influence of soluble factors derived from the ductal epithelium [34,36,37]. Although, to date, most of the supporting evidence for this concept has been derived from animal (mainly rodent) studies, the results of the present investigation suggest that similar regulatory and/or trophic influences, exerted by the ductal epithelia, may be crucial for appropriate and sustained human beta cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Although a small early delay in gastric emptying has been observed after a single dose of vildagliptin (19), vildagliptin does not slow gastric emptying in a clinically meaningful manner after multiple dosing in patients with T2DM (20). Vildagliptin has been associated with attenuated insulin resistance during meals (12,21). It is not known, however, whether DPP-4 inhibition improves peripheral glucose utilization.…”
mentioning
confidence: 99%
“…Four mechanisms are reported to be involved in cell mass alteration: replication of pre-existing differentiated cells (cell proliferation), differentiation from precursor cells (neogenesis), programmed cell death (apoptosis), and change in individual cell volume [10][11][12][13]. O'Brien and colleagues found that -cell apoptosis precedes infiltration of inflammatory cells into the islets and it has been proposed that apoptosis is the mode of -cell death responsible for the development of spontaneous diabetes in non-obesediabetic (NOD) mice [14] and in the multiple low-dose streptozotocin diabetes in C57BL/6 mice [15].…”
Section: Introductionmentioning
confidence: 99%